An investigation of the pattern and mechanism of comorbidity in patients with Hashimoto’s thyroiditis - Zhao, Caihong; Xiong, Haodong; Zhu, Lingfei; Adali, Azijiang; Yu, Weijie; Tan, Simiao; Wang, Shuying; Zhao, Chengbowen; Lin, Yan; Wei, Zinan; Huang, He; Peng, Xinyu (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate comorbidity patterns and potential pathogenic mechanisms in patients with Hashimoto’s thyroiditis (HT).MethodsPatients with HT who visited the outpatient clinic of the Thyroid Department at Dongzhimen Hospital, Beijing University of Chinese Medicine, between June 2021 and December 2024 were included. Association rule analysis and logistic regression analysis were performed using SPSS 25.0 and SPSS Modeler 18.0 to identify comorbidity patterns. Disease targets were screened using the GeneCards database, and protein interaction networks for intersecting targets were constructed using STRING and Cytoscape. GO function and KEGG pathway enrichment analyses were performed with Metascape to uncover relevant targets and potential pathways associated with comorbidities in patients with HT.ResultsAmong 429 patients with HT, 348 had comorbidities, resulting in a comorbidity prevalence of 81.19%. Association rule analysis identified thyroid nodules (TN) as the core binary comorbidity. The combination of TN and hyperplasia of the mammary gland (HMG) was central to ternary comorbidities, while the trio of TN, HMG, and uterine leiomyomas (UL) characterized quaternary comorbidities. Being a woman and advancing age were associated with increased risk of comorbidities, whereas levothyroxine sodium (L-T4) therapy was linked to reduced risk. Core targets associated with comorbidity prediction included AKT1, TP53, EGFR, INS, and TNF. Key pathways involved were the cancer pathway and PI3K–Akt signaling pathway.ConclusionThe high prevalence of comorbidities in patients with HT warrants increased clinical attention within the medical community.